2020
DOI: 10.3390/en13113023
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Storage Using Metallic Phase Change Materials for Bus Heating—State of the Art of Electric Buses and Requirements for the Storage System

Abstract: Battery-powered electric buses currently face the challenges of high cost and limited range, especially in winter conditions, where interior heating is required. To face both challenges, the use of thermal energy storage based on metallic phase change materials for interior heating, also called thermal high-performance storage, is considered. By replacing the battery capacity through such an energy storage system, which is potentially lighter, smaller, and cheaper than the batteries used in buses, an overall r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…For a favored design option selected here, maximum systemic storage densities of 201 Wh/kg with a charging power of 6.4 kW were achieved by simultaneous low maximum heat losses of 76 W for a permitted exterior surface temperature of 60 • C. Comparing the thermal storage densities with those of battery powered PTC heaters operating in a range from 100 Wh/kg to 180 Wh/kg [15,36] for today's commercial Li-Ion systems, the vehicle-systemic and even cost potentials are obviously in spite of drawbacks regarding exergetic potentials. For proofing and confirming the storage concept, a test rig was erected focusing experimental investigations on the charging process and model validations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a favored design option selected here, maximum systemic storage densities of 201 Wh/kg with a charging power of 6.4 kW were achieved by simultaneous low maximum heat losses of 76 W for a permitted exterior surface temperature of 60 • C. Comparing the thermal storage densities with those of battery powered PTC heaters operating in a range from 100 Wh/kg to 180 Wh/kg [15,36] for today's commercial Li-Ion systems, the vehicle-systemic and even cost potentials are obviously in spite of drawbacks regarding exergetic potentials. For proofing and confirming the storage concept, a test rig was erected focusing experimental investigations on the charging process and model validations.…”
Section: Discussionmentioning
confidence: 99%
“…Within the solid honeycomb wall (zone II), the radial transient heat balance is based on Equation (15):…”
Section: Effective Radiation Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials have different levels or kinds of properties. The use of metallic PCMs like other materials used for a similar purpose can transport heat away from a critical device meaning that they can buffer the temperature of a device during periods of transient high-power operation [80] . They then can store that heat using the latent heat of fusion.…”
Section: Metallics Used As Pcmsmentioning
confidence: 99%
“…The study showed that the designed THS could increase the vehicle's range in winter conditions by up to 26.7% for the chosen driving scenario. An even higher potential is expected for vehicles with higher heating demand, like buses [11].…”
Section: Introductionmentioning
confidence: 99%